Multiple roles for basement membrane proteins in cancer progression and EMT - Banerjee, Samarpita; Lo, Wen-Cheng; Majumder, Payel; Roy, Debleena; Ghorai, Mimosa; Shaikh, Nusrat K.; Gundamaraju, Rohit (Elsevier Gmbh, 2022)
Metastasis or the progression of malignancy poses a major challenge in cancer therapy and is the principal reason for increased mortality. The epithelial-mesenchymal transition (EMT) of the basement membrane (BM) allows cells of epithelial phenotype to transform into a mesenchymal-like (quasi-mesenchymal) phenotype and metastasize via the lymphovascular system through a metastatic cascade by intravasation and extravasation. This helps in the progression of carcinoma from the primary site to distant organs. Collagen, laminin, and integrin are the prime components of BM and help in tumor cell metastasis, which makes them ideal cancer drug targets. Further, recent studies have shown that collagen, laminin, and integrin can be used as a biomarker for metastatic cells. In this review, we have summarized the current knowledge of such therapeutics, which are either currently in preclinical or clinical stages and could be promising cancer therapeutics.Data availability: Not applicable
Keywords: Basement membrane; EMT; Metastasis; Collagen; Laminin; Integrin; Squamous-Cell Carcinoma; Breast-Cancer; I Collagen; Colorectal-Cancer; Gene-Expression; Malignant Phenotype; Biological-Activity; Extracellular-Matrix; Promotes; Integrin